2001
DOI: 10.1128/aem.67.9.3810-3818.2001
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic Analyses of Escherichia coli O157:H7 and O157 Nonmotile Isolates Recovered from Beef Cattle and Carcasses at Processing Plants in the Midwestern States of the United States

Abstract: Escherichia coli O157:H7 and O157 nonmotile isolates (E. coli O157) previously were recovered from feces, hides, and carcasses at four large Midwestern beef processing plants (R. O. Elder, J. E. Keen, G. R. Siragusa, G. A. Barkocy-Gallagher, M. Koohmaraie, and W. W. Laegreid, Proc. Natl. Acad. Sci. USA 97:2999-3003, 2000). The study implied relationships between cattle infection and carcass contamination within single-source lots as well as between preevisceration and postprocessing carcass contamination, base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
67
1
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 101 publications
(78 citation statements)
references
References 51 publications
8
67
1
2
Order By: Relevance
“…Previous studies had suggested that E. coli O157:H7 prevalence in feces was correlated with the pathogen's prevalence on carcasses (11,18,24,25), and the prevalence levels of both E. coli O157:H7 and Salmonella in cattle feces have been investigated in depth. Although it is dif cult to compare results from various studies because of differences in methodology, preliminary data have suggested that the MRU and MRU-TT methods are at least as sensitive as previously employed methods (12).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had suggested that E. coli O157:H7 prevalence in feces was correlated with the pathogen's prevalence on carcasses (11,18,24,25), and the prevalence levels of both E. coli O157:H7 and Salmonella in cattle feces have been investigated in depth. Although it is dif cult to compare results from various studies because of differences in methodology, preliminary data have suggested that the MRU and MRU-TT methods are at least as sensitive as previously employed methods (12).…”
Section: Discussionmentioning
confidence: 99%
“…When contamination exceeds this limit, the interventions will be overwhelmed and carcass contamination will not be eliminated. The incoming E. coli O157:H7 contamination of most concern is that found on the hides of cattle entering the processing facility (4,5,7,20). Recently, postharvest interventions have been focused on the hide in an attempt to keep contamination levels from overwhelming downstream antimicrobial interventions applied to the carcass (7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%
“…Samples were processed according to methods previously described with slight modifications (5,6). Carcass, hide, and truck sponge samples were enriched with 80 ml of TSB after the 250-l aliquot for enumeration was removed.…”
Section: Animalsmentioning
confidence: 99%
“…Nou et al (23) demonstrated that hide dehairing, which in effect sanitizes the animal hide, can greatly reduce carcass bacterial loads and eliminate E. coli O157. Barkocy-Gallagher et al (3) showed that .66% of the E. coli O157:H7 isolates from beef carcasses identi ed late in processing could be tracked by pulsed-eld gel electrophoresis to the same carcass early in processing. This nding indicates that the E. coli O157 population associated with the animal or carcass persisted throughout processing.…”
Section: Enumeration Of Aerobic Bacteria and Enterobacteriaceaementioning
confidence: 99%